Dinamika dan Rekonstruksi Konsep Zakat dalam Hukum Islam Kontemporer di Era Ekonomi Digital - Damar Chandra Prasetyo; Muhammad Rafi Athaya Santoso; Kaia Hati (Journal of Legal, Political, and Humanistic Inquiry, 2025)
Zakat is one of the essential instruments in Islamic law that embodies both worship and socio-economic dimensions. In classical jurisprudence, zakat was understood as an individual obligation limited to specific assets such as gold, silver, agricultural products, and livestock. With the emergence of modern forms of wealth such as professional income, stocks, and digital assets, a reinterpretation of zakat law is needed to maintain its relevance. This study aims to analyze the transformation of zakat within the framework of contemporary Islamic law using a normative juridical approach through library research. The results show that Islamic law demonstrates strong adaptability to social and economic changes while maintaining the principles of justice, welfare, and public benefit. Zakat has evolved from a personal act of worship into a socio-economic instrument that plays a vital role in poverty alleviation and equitable distribution of wealth. The transformation of zakat reflects the dynamic nature of Islamic law in addressing modern challenges without neglecting its core religious principles.